Beyond Resolution: Daoist Principles and the Coexistence with Grief - Fasiha Nargis , Fahad Javed Baig , Sumera Arshad and Misbah Sattar (Journal of Daoist Studies, 2026)
Grief is a global intense human experience that encompasses emotional, psychological, and existential perspectives. Contemporary western psychological models of grief including stage-based, task-oriented, and continuing bonds frameworks share an implicit metaphysics of resolution: grief is construed as a disorder of the self to be processed, resolved, or transcended. This conceptual paper offers a targeted philosophical framework derived from Daoist philosophy that integrates psychological understandings of bereavement adjustment with three fundamental principles: Wu Wei (non-forcing), acceptance of impermanence, and Yin-Yang balance. Rather than treating grief as a condition requiring resolution, Daoist philosophy reconceptualizes it as a natural dimension of human existence to be engaged with rather than overcome. The paper argues that these three principles offer a coherent, internally consistent philosophical foundation capable of complementing existing grief theories and informing therapeutic approaches. Drawing on classical Daoist texts, including the Tao Te Ching and the Zhuangzi, the framework proposes that grief adjustment may be better understood not as elimination of suffering but as the cultivation of harmonious coexistence with loss. Implications are considered for cross-cultural grief theory, clinically informed Daoist studies, and the broader challenge of resolution-bias in bereavement research.